2002
DOI: 10.1021/jp021276r
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Charge Separation of N,N,NN‘-Tetramethylbenzidine in Chromium Ion-Exchanged Zeolite X at Room Temperature

Abstract: Chromium ion-exchanged zeolite X microporous materials were examined for the photoionization of N,N,N‘N‘-tetramethylbenzidine (TMB) with 320-nm irradiation at room temperature. Photoionization of chromium-containing zeolite X results in the formation of N,N,N‘N‘-tetramethylbenzidine radical cations (TMB+ •), which are characterized by electron spin resonance (ESR) and diffuse reflectance spectroscopy (DRS). ESR studies indicate that Cr(V) acts as an electron acceptor. The photoyield and stability of the photop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…The bands observed in the UV region in Cr(V) doped Ca 2 PO 4 Cl, vanadates, and phosphates have been assigned to O → Cr 5+ charge transfer bands. The ESR studies described later also suggest that Cr(V) is present in the calcined samples. Thus, we assign the two optical bands in the UV region to Cr(V) formed by oxidation of Cr(III) during calcination consistent with previous reports from our laboratory. ,, The two bands in the visible region observed near 450 and 620 nm for CrAPSO-5 are typically assigned to d−d transitions of Cr(III) either in an octahedral or in a distorted octahedral environment. These are assigned to 4 A 2g → 4 T 1g and 4 A 2g → 4 T 2g transitions.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The bands observed in the UV region in Cr(V) doped Ca 2 PO 4 Cl, vanadates, and phosphates have been assigned to O → Cr 5+ charge transfer bands. The ESR studies described later also suggest that Cr(V) is present in the calcined samples. Thus, we assign the two optical bands in the UV region to Cr(V) formed by oxidation of Cr(III) during calcination consistent with previous reports from our laboratory. ,, The two bands in the visible region observed near 450 and 620 nm for CrAPSO-5 are typically assigned to d−d transitions of Cr(III) either in an octahedral or in a distorted octahedral environment. These are assigned to 4 A 2g → 4 T 1g and 4 A 2g → 4 T 2g transitions.…”
Section: Resultssupporting
confidence: 90%
“…We have earlier observed that Cr containing SAPO-5 and zeolite X show higher yields of methylphenothiazine and N , N , N ‘, N ‘-tetramethylbenzidine cation radical as compared to other transition metal ion containing microporous materials. ,, Thus, it is of interest to study the photoionization of pyrene in Cr containing SAPO-5 materials. The ESR spectra of pyrene-impregnated Cr(III) liquid state ion-exchanged SAPO-5 show a signal at g = 2.003 due to Py +• assigned to pyrene cation radical prior to irradiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our nding is consistent with the previous study on TMB cation-free radicals. 28 These results imply that a Co 3 O 4 NPs-CNNT hybrid in the presence of TMB and H 2 O 2 should show the superior peroxidase-like redox activity because the charge-transfer of TMB cation-free-radicals 29 and the Fenton-based reaction 30…”
Section: Binding Mechanism Of Between Co 3 O 4 Nps and A Cnnt Using T...mentioning
confidence: 96%
“…[16][17][18][19][20] TMB is also an efficient photosensitizer for reductions of various substrates in both solution and micelles. [21][22][23][24] The spectral and electrochemical features of TMB seem well suited to address some of the key factors responsible for the kinetic and mechanistic differences, as well as similarities between homogeneous and heterogeneous electron transfer that we wish to discuss in this work.…”
Section: Introductionmentioning
confidence: 99%